1992
DOI: 10.1007/bf01715117
|View full text |Cite
|
Sign up to set email alerts
|

Thymidine kinase: a tumor marker with prognostic value for non-Hodgkin's lymphoma and a broad range of potential clinical applications

Abstract: Thymidine kinase (TK) is a cellular enzyme which is involved in a "salvage pathway" of DNA synthesis. It is activated in the G1/S phase of the cell cycle, and its activity has been shown to correlate with the proliferative activity of tumor cells. Additionally, certain viruses are able to induce cellular TK production and activity. Clinical studies have reported elevated serum TK levels in a variety of neoplasias. The majority of these studies concerned hematologic malignancies. TK seems to be a useful marker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0
3

Year Published

1992
1992
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 44 publications
2
64
0
3
Order By: Relevance
“…Our results raise the hypothesis that regulation of TK activity by growth factors, and therefore the cellular dNTP levels, could be a checkpoint to signal proliferating cells whether to continue the progression through the cell cycle or to enter a program of cell death by apoptosis. Deregulated expression of cellular TK activity has been reported to be correlated with tumorigenicity (12,13) and cell resistance to radiation (15). On the other hand, viral TK could be an apoptosis-inhibiting factor during productive or latent infection of cells with herpes simplex virus, acting perhaps in a concerted manner with the viral proteins ␥34.5 and ICP4, recently described as inhibitors of apoptosis (48,49).…”
Section: Fig 2 Expression Of Heterologous Hsv Thymidine Kinase In Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results raise the hypothesis that regulation of TK activity by growth factors, and therefore the cellular dNTP levels, could be a checkpoint to signal proliferating cells whether to continue the progression through the cell cycle or to enter a program of cell death by apoptosis. Deregulated expression of cellular TK activity has been reported to be correlated with tumorigenicity (12,13) and cell resistance to radiation (15). On the other hand, viral TK could be an apoptosis-inhibiting factor during productive or latent infection of cells with herpes simplex virus, acting perhaps in a concerted manner with the viral proteins ␥34.5 and ICP4, recently described as inhibitors of apoptosis (48,49).…”
Section: Fig 2 Expression Of Heterologous Hsv Thymidine Kinase In Bmentioning
confidence: 99%
“…Thymidine kinase is perhaps the best characterized of these enzymes; its substrates are thymidine and deoxyuridine, and it is inhibited by dTTP (4). It has been used as a malignancy marker for a variety of tumors (12,13), and tumor cells deficient in this enzyme show a lower oncogenic potential than the wild-type cells from which they derive (14). Moreover, a recent report has also demonstrated that TK is a major radioresponse determinant in rat glioma cells (15).…”
mentioning
confidence: 99%
“…A stable serum form of TK1 was identified already in 1980 and serum TK (s-TK) levels serve as a biomarker in many different malignant diseases, e.g., Hodgkin's and non-Hodgkin's lymphoma (NHL), acute myeloid leukemia (AML), lymphocytic leukemia (LL), and chronic LL (6)(7)(8). One report describes s-TK activity and lactate dehydrogenase (LDH) activity in dogs with malignant lymphoma (ML) (9).…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanismby which TKis released from dividing cells is not fully understood. It is thought that TKis an intracellular enzyme, and is probably not released into circulation by normal dividing cells (15). What does high serum TKimply in sarcoidosis?…”
Section: Discussionmentioning
confidence: 99%